IN VITRO ANTICANCER ACTIVITY OF LAMOTRIGINE AND 5-FLUOROURACIL INDIVIDUALLY AND IN COMBINATION ON HUMAN K562 AND COLO320HSR CELL LINES BY TRYPAN BLUE ASSAY - KATARIKONDA SUDHAKAR; MEDA RAMESH (International Journal of Pharma and Bio Sciences, 2014)
Cancer is the leading cause of disease for high mortality all over the world. Antitumor drug resistance and side effects of antitumor drugs are the most common problems in cancer chemotherapy. It is of great importance in considering the drugs having the anticancer activity and going for the new combination of cancer therapeutics for avoiding the problems of tumor drug resistance and side effects with a new therapeutic combinations and by lowering the dose of drugs. In the present study the anticancer activity of Lamotrigine and 5-Fluorouracil individually and in combination were determined on Colo 320HSR and K562 cell lines. And our results concluded that the both drugs individually and combination have better anticancer activity at higher concentrations.